(untitled) - Kovac, Bronislav (Doprava a spoje, 2007)
The issue of road vehicle recycling after the operational life time is analyzed in the article regarding the legislative of the European Union and its implementation to the laws of the Slovak republic. The article provides review of the European directives, laws and regulations valid in that area. Further, the categorization of a garbage created within evaluation of road vehicles scraps and scraps evaluation conditions are introduced. The article simultaneously shows emergent issue of the living environment quality solution from environmental point of view.